2012
DOI: 10.1111/j.1745-4549.2012.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Addition of Germinated Lupin Flour on the Physiochemical and Organoleptic Properties of Cookies

Abstract: Lupin is nutritious type of legumes and its nutritional value could be increased by germination. Substitution of wheat flour (WF) with germinated lupin flour (GLF) at levels of 10–50% was investigated for their effects on the physiochemical and organoleptic properties of cookies. Ash, fiber, protein and lipid contents increased in GLF and germinated lupin cookies (GLC) as level of replacement increased. However, carbohydrates in WF and control cookies (CC) were higher than GLF and GLC. Physical analysis for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…) since composite flours form aggregates with increased number of hydrophilic sites found within the oligosaccharides, polysaccharides, water‐soluble protein, and polar amino acids in legumes proteins. All of them which competing for the limited free water in the cookie dough . Other important characteristic of cereals and legumes is the amount of dietary fiber which has beneficial health implications for the consumer .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…) since composite flours form aggregates with increased number of hydrophilic sites found within the oligosaccharides, polysaccharides, water‐soluble protein, and polar amino acids in legumes proteins. All of them which competing for the limited free water in the cookie dough . Other important characteristic of cereals and legumes is the amount of dietary fiber which has beneficial health implications for the consumer .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, consumption of cookies with low nutritional value is an issue of concern specially in school‐age children since they need more protein per unit body weight compared to adults. Therefore, production of cookies with higher nutritional value is necessary . Other cereal alternatives like maize, rice, sorghum, and pearl millet have been explored as substitutes of wheat .…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of more than 8% germinated lupin flour is likely to affect the quality of muffins making them unacceptable. However, it has been shown that, substitution of germinated lupin flour up to 30% (as flour basis) had no significant affect on overall quality of the cookies (Obeidat et al, 2013).…”
Section: Texturementioning
confidence: 99%
“…Hence, it cannot be stated that the differences between the five different flours on one hand and LE addition on the other occurred due to the presence of gluten. Jayasena and Nasar-Abbas [26], Obeidat, Abdul-Hussain and Al Omari [47] and Bilgiçli and Levent [44] reported that cookie hardness increased with the addition of lupin flour in the cookie formulation. This can also be stated for other types of legume seeds, such as chickpeas [48], green lentils and navy beans [4].…”
Section: Cookie Formulationmentioning
confidence: 99%